Association between estimated glomerular filtration rate, urinary albuminuria-creatinine ratio, and stroke prevalence in patients with chronic kidney disease - Jianfeng Xiang; Mengli Tong; Dongrong Yu; Yinfeng Chen (Renal Failure)
Background With the global increase in chronic diseases, chronic kidney disease (CKD) and stroke have become major public health concerns. This study aims to investigate the relationship between estimated glomerular filtration rate (eGFR), urine albumin-to-creatinine ratio (UACR), and the incidence of stroke in a CKD population.Methods This cross-sectional study analyzed the relationship between eGFR, UACR, and prevalence of self-reported stroke in 6,037 participants using data from the National Health and Nutrition Examination Survey (NHANES) from 2007 to 2018. Multivariate logistic regression analysis was used to evaluate the association of eGFR, UACR with the incidence of stroke, and smoothing curve fitting was applied to explore the linear relationship between eGFR and stroke. To further explore the effect of eGFR on stroke risk, we performed subgroup analyses of demographic factors.Results After adjusting for confounding factors, eGFR was found to be significantly negatively associated with stroke risk. Compared with participants with an eGFR ≥ 90 mL/min/1.73 m2, the risk of stroke was increased in those with an eGFR of 60–90 (OR = 1.78; 95% CI = 1.18–2.69), 30–60 (OR = 2.26; 95% CI = 1.49–3.44), and <30 mL/min/1.73 m2 (OR = 3.14; 95% CI = 1.74–5.65). In the unadjusted model, patients with UACR of 30–300 mg/g had a slightly lower risk of stroke than those with UACR < 30 mg/g (OR = 0.70, 95% CI = 0.57–0.86); however, this association was not seen after adjusting for potential confounders.Conclusions This study identified a negative linear correlation between eGFR and stroke in CKD patients.